Preischemic efferent vagal stimulation increases the size of myocardial infarction in rabbits. Role of the sympathetic nervous system - Buchholz, Bruno (2012)
The vagal nerve stimulation (VNS) has been tested for the treatment of chronic heart failure in humans (Schwartz et al., 2008). However, many of the effects of parasympathetic stimulation in ischemic heart disease are still unknown. Kawada et al. have shown a significant increase in acetylcholine (Ach) levels in the ventricular myocardium subjected to VNS (Kawada et al., 2000). Since, Ach has been implicated in the mechanism of ischemic preconditioning (Yellon & Downey, 2003), we can hypothesize that VNS applied before ischemia may reduce myocardial infarct size by a release of Ach. However, under certain experimental conditions, the two divisions of the autonomic nervous system (sympathetic and parasympathetic) can be activated. Therefore, co-activation of the sympathetic nervous system could generate a situation adverse and contrary to the possible beneficial effect expected for VNS.